2018
DOI: 10.1002/brb3.1150
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate and sex ratio in multiple sclerosis in Lithuania

Abstract: ObjectivesTo determine the temporal changes in incidence rates of multiple sclerosis (MS) over the past 15 years in Lithuania with prediction up to 2020, and to estimate female‐to‐male sex ratio and its changes among MS patients.Materials and MethodsWe conducted a descriptive incidence study. The crude incidence rates (CIR) were calculated using 15‐year period, sex, age‐groups, and the number of newly registered MS patients. Standardized incidence rates (SIR) were calculated using European standard in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Overall the sex ratio was stable over the period, in contrast to other studies finding a marked increase in the female-to-male sex ratio of MS incidence in many countries over the past 50 years 4 , 27 , 28 . In Argentina, Rojas et al found a variation of 1.8–2.7 over 50 years 4 , In Lithuania, Valadkeviciene et al found a variation of 1.5–2 29 . This change in the female-to-male ratio is generally driven by an increasing MS incidence in women rather than a decline in that of men.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the sex ratio was stable over the period, in contrast to other studies finding a marked increase in the female-to-male sex ratio of MS incidence in many countries over the past 50 years 4 , 27 , 28 . In Argentina, Rojas et al found a variation of 1.8–2.7 over 50 years 4 , In Lithuania, Valadkeviciene et al found a variation of 1.5–2 29 . This change in the female-to-male ratio is generally driven by an increasing MS incidence in women rather than a decline in that of men.…”
Section: Discussionmentioning
confidence: 99%
“…The observed rise in F/M ratio cannot be easily explained by genetics or by new diagnostic technologies or increased awareness, which would apply to both sexes. Results of numerous population-based studies in different parts of the world and the meta-analyses suggest that the recent increase of MS incidence provide some evidence that this has primarily resulted from an increase in the incidence of MS among women [77][78][79][80][81][82];…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is defined as an immune-mediated inflammatory, neurodegenerative, and demyelinating disease that impacts the central nervous system (CNS) in young individuals [1,2]. Approximately 1 to 2.5 million people (mostly women, with a female-to-male ratio of 2:1) around the world are affected by MS [3]. A variety of genetic and environmental factors, including immune system dysregulation, central nerve demyelination [4,5], vitamin D deficiency, Epstein-Barr virus, and smoking [6], have been considered as possible etiologies of MS.…”
Section: Introductionmentioning
confidence: 99%